Characterization of elderly patients with abdominal surgery. Intensive Care Unit. Enrique Cabrera Hospital. 2015-2016 - Antuan Quintero Infante; Albadio Isidro Perez Assef; Jorge Díaz Mayo (Universidad de Ciencias Médicas de La Habana, 2019)
Introduction:  Several studies report that patients older than 60 years are three times more likely to be admitted to hospitals for surgery than younger members of the population.  Objective: To characterize patients older than 60 years admitted with abdominal surgery.  Materials and methods:  A descriptive, retrospective, and longitudinal study was carried out.  The clinical histories of 88 patients older than 60 years admitted with abdominal surgery to the Intensive Care Unit of Enrique Cabrera General Teaching Hospital during the years 2015-2016 who fulfilled the inclusion and exclusion criteria were reviewed.  Descriptive statistics was used to summarize quantitative and qualitative variables.  Results: Of the patients admitted, 40,9% died.  The greatest mortality was observed in females (48,9%) and patients older than 81 years (48,1%).  Arterial hypertension (29,9%) was the most frequent pathological antecedent.  Mortality after peritonitis was 72,0%. The patients with acute renal failure, septic shock, multiple organ dysfunction syndrome, and mechanical ventilation presented a mortality rate higher than 80%.  E. coli was isolated in 12,5% of patients.  Conclusions: The factors related to decease were: patients older than 81 years of age, diagnosis of peritonitis, need of mechanical ventilation, presence of acute renal failure, septic shock, multiple organ dysfunction syndrome, and Acute Physiology and Chronic Health with an evaluation of more than 16 points.  The most isolated germ was E. coli, and the respiratory system was the most frequent location. Keywords: Elderly patients, abdominal surgery, mortality, peritonitis, mechanical ventilation, sepsis.